2009
DOI: 10.1007/s10551-009-0116-y
|View full text |Cite
|
Sign up to set email alerts
|

‘If I Should Fall From Grace…’: Stories of Change and Organizational Ethics

Abstract: ABSTRACT. Although studies in organizational storytelling have dealt extensively with the relationship between narrative, power and organizational change, little attention has been paid to the implications of this for ethics within organizations. This article addresses this by presenting an analysis of narrative and ethics as it relates to the practice of organizational downsizing. Drawing on Paul Ricoeur's theories of narrative and ethics, we analyze stories of organizational change reported by employees and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 72 publications
1
50
0
Order By: Relevance
“…However, as the review of consequentialist ethics demonstrated, not all approaches to ethics necessarily have beneficial results. Whilst leaders who adopt utilitarian ethics are likely to pursue the interests of all their stakeholders, leaders who adopt more individual-egotistic ethics are more likely to put their own interests before that of other stakeholders (Clark 2008;du Plessis 2008;Kanungo and Mendonca 1996;Partnoy 2003;Porter 2008;Rhodes et al 2010;Sunderland 2008Sunderland , 2009.…”
Section: Discussion: the Case For Claritymentioning
confidence: 99%
See 2 more Smart Citations
“…However, as the review of consequentialist ethics demonstrated, not all approaches to ethics necessarily have beneficial results. Whilst leaders who adopt utilitarian ethics are likely to pursue the interests of all their stakeholders, leaders who adopt more individual-egotistic ethics are more likely to put their own interests before that of other stakeholders (Clark 2008;du Plessis 2008;Kanungo and Mendonca 1996;Partnoy 2003;Porter 2008;Rhodes et al 2010;Sunderland 2008Sunderland , 2009.…”
Section: Discussion: the Case For Claritymentioning
confidence: 99%
“…Indeed, as will be discussed below, Lewin's ethical view of change lies at the heart of the Organisation Development (OD) movement which dominated the field of change up to the early 1980s (Burnes 2004(Burnes , 2009a. Alongside the rise of charismatic-transformational leadership has been the growing volume of calls for organisations to act in an ethical fashion (Dunphy et al 2007;Jones et al 2000;Hitt et al 2009;Rhodes et al 2010;Wines 2008). Prominent in this respect has been the promotion of corporate social responsibility (CSR) by national governments and international bodies, especially the United Nations (Garriga and Melé 2004;Li and Zhang 2010;Matten and Moon 2004;Renouard 2011;United Nations 2010).…”
Section: Leadership and Ethicsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is crucial that colleges make these policy related decisions with sound judgment and comprehensive data instead of making retention choices "lacking common definitions and understandings" that "lead to unclear communication, and worse, ineffective practice" (Wolf-Wendel, Ward & Kinzie, 2009, p. 407). Rhodes, Pullen and Clegg (2010) contended that the central storyline of the organizational context at any particular time helps to define that organization's decision-making values and restricts choices, explaining that "the dominance and repetition of narratives limit the possibilities of organizational ethics" (p. 536). Rhodes, et al (2010) further elaborated on this theory by stating that those who exercise power often claim ethical justification for their actions.…”
Section: Student Attritionmentioning
confidence: 99%
“…Rhodes, Pullen and Clegg (2010) contended that the central storyline of the organizational context at any particular time helps to define that organization's decision-making values and restricts choices, explaining that "the dominance and repetition of narratives limit the possibilities of organizational ethics" (p. 536). Rhodes, et al (2010) further elaborated on this theory by stating that those who exercise power often claim ethical justification for their actions.…”
Section: Student Attritionmentioning
confidence: 99%